1995
DOI: 10.1071/ch9951819
|View full text |Cite
|
Sign up to set email alerts
|

New Macrocyclic Ligands. VI. 20- to 22-Membered Dibenzo-Substituted Rings Incorporating Mixed Nitrogen, Oxygen and/or Sulfur Donor Atoms

Abstract: The syntheses and characterization of 10 dibenzo-substituted macrocycles incorporating mixed nitrogen, oxygen and/or sulfur donor sets are reported. The new systems, which incorporate six potential donor sites, extend the range of related (potentially tetradentate and pentadentate) macrocyclic systems reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[12] We have found that a similar procedure may successfully be employed for the preparation of the reduced macrocycle 2. The FAB mass spectrum …”
Section: Macrocycle 2 and Its Metal Complexesmentioning
confidence: 96%
See 1 more Smart Citation
“…[12] We have found that a similar procedure may successfully be employed for the preparation of the reduced macrocycle 2. The FAB mass spectrum …”
Section: Macrocycle 2 and Its Metal Complexesmentioning
confidence: 96%
“…Most efforts to date have focused on its use in the synthesis of oxaazapolyamine macrocycles as complexing agents for transition metal or heavy metal ions. [11][12][13][14] In contrast, little has been reported on its use in the synthesis of Schiff-base macrocycles and their metal complexes. [15][16][17] An important aspect of the present work has been the synthesis of two novel dibenzo-substituted Schiff-base macrocycles derived from O 1 ,O 7 -bis(2-formylphenyl)-1,4,7-trioxaheptane, specifically the 26-membered N 2 O 6 -donor macrocycle 1 and the 20-membered N 4 O 3 -donor pendantarm macrocycle 3 (Scheme 1).…”
Section: Introductionmentioning
confidence: 92%
“…For related literature, see: Adam et al (1981); Barczynśki et al (2007); Davis et al (1995); Higa et al (2007); Jiang et al (2007); Michalska et al (2007); Zhou et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…The use of macrocyclic ligands for the formation of selective metal complex has received considerable attention over many years (Davis et al, 1995). The method for the synthesis of the title complex has been reported (Adam et al, 1981).…”
Section: Commentmentioning
confidence: 99%
“…One of the most convenient and widely used methods for the production of dibenzotetraazacrown ethers is the reaction of dicarbonyl compounds (dialdehydes, acid dichlorides) with the corresponding diamines. Thus, this approach was used successfully by American [43] and Australian [44] investigators for the synthesis of macrocycles of types 21a-c, 22, and 23 respectively. The Schiff bases were not isolated from the reaction mixture, and they were reduced in situ by slow addition of NaBH 4 to the solution.…”
mentioning
confidence: 98%